6 Silent cerebral microinfarction following mitral valve surgery. (6th June 2022) - Gorecka, Miroslawa; Nejadhamzeeigilani, Hamed; Craven, Thomas P; Chew, Pei G; Dobson, Laura E; Brown, Louise; Chowdhary, Amrit; Jex, Nicholas; Thirunavukarasu, Sharmaine; Sharrack, Noor; Javed, Wasim; Kotha, Sindhoora; et al.
Abstract : Introduction: Mitral regurgitation (MR) is the second most common valvular pathology worldwide. When untreated, severe MR is associated with significant morbidity and mortality. Mitral valve surgery is recommended in symptomatic patients and those with evidence of adverse left atrial or left ventricular remodelling. Although uncommon, stroke is a recognised complication of mitral valve surgery and is associated with unfavourable outcomes. While silent cerebral microinfarction has been described following cardiac surgery, its incidence in mitral valve surgery and its impact on quality of life is presently unknown. The main aim of this study was to assess the incidence of perioperative cerebral microinfarction following mitral valve surgery and its impact on medium-term health-related quality of life (HRQoL). MethodsCerebral diffusion-weighted magnetic resonance imaging (DWI-MRI) was conducted pre-operatively and prior to discharge in 31 patients undergoing mitral valve surgery for mitral regurgitation. Blinded analysis was conducted by a neuro-radiologist. HRQoL assessment was undertaken at baseline and at a 6-month follow up with EuroQoL-5 dimensions (EQ-5D-5L) and Hospital Anxiety and Depression Scale (HADS) questionnaires. Results: Thirty-one patients underwent paired cerebral DWI-MRI (mitral valve replacement (MVR) n=16 [52%] and mitral valve repair (MVr) n=15 [48%]). Prevalence of atrial fibrillation was similar in both groups (MVR n=9 [56%] vs. MVr n=7 [47%], p=0.59). Peri-operative cerebral microinfarction occurred in 9 patients (29%). Embolic events were numerically higher in the MVR group versus MVr group, but not statistically significant (n=7 [44%] vs. n=2 [13%], p=0.06). Presence of multiple lesions, large lesions >5 mm, small lesions <5 mm and the total number of lesions did not differ significantly between the two groups. Median volume of lesions was higher in the MVR group versus MVr (0 [0–0.4] vs 0[0–0], p=0.04). (Table 1) There was no difference in the mean change in HRQoL during 6 m follow up between patients with peri-operative cerebral microinfarction and those with no detectable embolic events. (Table 2) Within group comparison (MVR group and MVr group) also did not demonstrate any significant difference. Conclusions: Peri-operative cerebral microinfarction occurred in almost a third of patients undergoing mitral valve surgery, with higher volume of lesions following MVR. These lesions however, did not exhibit significant impact on medium term health-related quality of life. Conflict of Interest: None